Pengaruh Lama Pemasangan Infus dengan Kejadian Flebitis pada Pasien Rawat Inap di Bangsal Penyakit Dalam dan Syaraf Rumah Sakit Nur Hidayah Bantul - Imram Radne Rimba Putri (Alma Ata University Press, 2016)
Infusion is one invasive procedure performed in a hospital. Inpatient therapy and intravenous fluids are given continuously in the long term will increase the likelihood of complications from infusion, one of which is the occurrence of phlebitis. The purpose of this study was to determine the effect of treatment duration infusion with the incidence of phlebitis in patients on the ward and neurological disease in the Nur Hidayah hospital in Bantul. This research is an analytic observational study with cross sectional approach, the number of samples is determined by calculation slovin as many as 133 people, with the sampling technique used purposive sampling. Data results from this study showed that respondents with a longer infusion <3 days a total of 37 respondents (32.8%) who did not have phlebitis 31 respondents (10.8%) and those with phlebitis 6 respondents (26.2%). As for respondents with a longer infusion ≥3 days as many as 76 respondents (67.2%) who experienced phlebitis 74 respondents (53.8%) and who had not had phlebitis 2 respondents (22.2%). Based on the results of data analysis using chi-square test values obtained p-value of 0.000, which means the value significantly smaller than the significance level α: 0.05, it means that the research hypothesis is accepted. In conclusion, that there is a long infusion influence on the incidence of phlebitis. Therefore, it may be advisable for the health care team in a hospital for treatment of patients infusion according to the procedure, especially for patients with infusion of more than 3 days, to avoid the occurrence of phlebitis.